2021
DOI: 10.1097/jcp.0000000000001409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exenatide Use on Cognitive and Affective Functioning in Obese Patients With Type 2 Diabetes Mellitus

Abstract: Purpose/Background: Glucagon-like peptide-1 (GLP-1) is a molecule used to treat type 2 diabetes mellitus (T2DM). Given their widespread expression in the nervous system, GLP-1 receptors also play a role in regulating mood and cognitive function. Here, we aimed to compare obese patients with T2DM, with or without exenatide (a GLP-1R agonist) use on cognitive and affective functioning. Methods/Procedures: A total of 43 patients with T2DM (23 on exenatide and 20 without exenatide) were evaluated with the Snaith-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…However, studies with non-significant findings were either based on small sample sizes or were not focused on DM patients. Although Eren-Yazicioglu et al (2021) reported that exenatide was associated with higher depressive scores indirectly through its effect on perceived stress, their study participants already had lifetime or current psychiatric diagnosis at baseline, which was different from our study (we excluded those with prior anxiety or depression diagnosis at baseline).…”
Section: Discussionmentioning
confidence: 62%
“…However, studies with non-significant findings were either based on small sample sizes or were not focused on DM patients. Although Eren-Yazicioglu et al (2021) reported that exenatide was associated with higher depressive scores indirectly through its effect on perceived stress, their study participants already had lifetime or current psychiatric diagnosis at baseline, which was different from our study (we excluded those with prior anxiety or depression diagnosis at baseline).…”
Section: Discussionmentioning
confidence: 62%
“…A total of 15 studies evaluated the association of incretin‐based therapies on cognitive function in patients with type 2 diabetes mellitus 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 31 , 32 , 33 , 34 , with eight included in our meta‐analysis 17 , 18 , 20 , 21 , 22 , 23 , 26 , 27 . Of the eight eligible studies, four were RCTs and four were cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies were not included in our meta‐analysis. Of these seven studies, three of these studies did not have specific values for MMSE 19 , 24 , 25 , and four of these studies used other cognitive evaluation tools 31 , 32 , 33 , 34 , respectively. Detailed information of 14 studies is showed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Therapy continued for another year in the good responders 28 43 Patients with T2DM and obesity, with overt hypogonadism and erectile dysfunction 28 Achieving normal serum testosterone levels Improving erectile dysfunction Reducing BW Improvement in other metabolic parameters (glucose, BP, and lipids) glutamatergic transmission in the brain, GLP-1 RAs may decrease palatable food and substance consumption [122]. However, a cross-sectional study reported no direct effect of EXE use on depressive scores compared to the group of diabetic patients with obesity not on GLP-RAs [129].…”
Section: Clinical Datamentioning
confidence: 99%
“…By changing the dopaminergic and glutamatergic transmission in the brain, GLP-1 RAs may decrease palatable food and substance consumption [ 122 ]. However, a cross-sectional study reported no direct effect of EXE use on depressive scores compared to the group of diabetic patients with obesity not on GLP-RAs [ 129 ].…”
Section: Central Nervous System Disordersmentioning
confidence: 99%